Error-related negativity (ERN) as a transdiagnostic endophenotype for irritability traits in a comunity sample : a rdoc perspective - Souza, Ana Maria Frota Lisboa Pereira de (2017)
Mental disorders present difficulties in the research of their mechanisms, considering the high levels of comorbidity and the lack of specific neuroscience data to evaluate them. Estipulating deficit circuits in the disorders and the best treatment is a complex task, given the limited comprehension of the factors that correlate to the disorders. The utilization of biomarkers has proved an efficient and reliable alternative to provide precise diagnosis. Among the biomarkers, the Error-Related Negativity component, an event-related cortical potential, has presented high indexes of stability and validity in correlating to anxiety, obsessive, and mood-related mental disorders. The present dissertation evaluated irritability traits in a community sample, using a Flanker task, that has consistently elicited Error-Related Negativity according to the literature. Our results corroborate literature and found a frontocentral negativity, that peaked around 100ms after the commission of an error in the Flanker Task. However, our manipulation of negative feedback did not support literature, and ERN amplitudes were less enhanced post negative feedback. The relationship between irritability and ERN remains unclear. Future studies should, therefore, address these questionings.